Further investigations on a unique range set under weight 0 and 1 - Banerjee, A.; Maity, S. (Carpathian Mathematical Publications, 2022)
In this paper, we have found the most generalized form of the famous Frank-Reinders polynomial. With the help of this, we have investigated the unique range set of a meromorphic function under two smallest possible weights namely 0 and 1. Our results extend some existing results in the literature.